Language Interference of Bimanese to the Indonesian Language: A Case Study of Community in Kampung Muhajirin, Bima - Irsyadi Shalima; Nurnaningsih Nurnaningsih (Universitas Tidar, 2018)
This research is initiated by the error use of Indonesian language by the community living in Kampung Muhajirin, Bima due to interference phenomenon. The errors occur in various linguistic aspects. This study aims to determine the interference forms of Bimanese language to the Indonesian language based on the characteristics differences between Bimanese and Indonesian language. One of the most distinct characteristics of both languages is that Bimanese is a vocalist language, while the Indonesian language is not a vocalist. The data were collected by observation and recording technique. The researchers observed the linguistic phenomenon in Kampung Muhajirin and recorded by a tape recorder. Finally, the data were analyzed and transcribed in orthographic writing. The finding showed that the interference of Bimanese language to the Indonesian language occurs on the aspects of phonological, lexical, and grammatical. Phonological interference causes the vowel sound disappeared at the end of the word. Lexical interference causes mixed code. Grammatical interference causes word order error.